Proceedings of the 8th International Conference on Fluid Flow, Heat and Mass Transfer (FFHMT'21) 2021
DOI: 10.11159/ffhmt21.140
|View full text |Cite
|
Sign up to set email alerts
|

A CFD/DEM Approach to Determine the Flow Resistance of Randomly Packed Bed of Crushed Rock Particles

Abstract: Packed beds of crushed rock particles are typically encountered in the thermal energy storage system at a solar thermal power plant. Rocks have irregular shapes, and tend to pack with their long axes in a horizontal plane. As a results its resistance to airflow is anisotropic. Designing a bed for effective charging and discharging cycles, depends on an accurate prediction of the flow distribution through it. Ellipsoids are mathematically simple shapes that characterise crushed rock particles reasonably success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Among these techniques, the coupled computational fluid dynamics and discrete element method (CFD‐DEM) has raised much attention because of its advantages in computational efficiency, especially compared with the Lattice Boltzman‐DEM coupling (LB‐DEM) 14 and pore‐scale finite volume‐DEM coupling (PFV‐DEM) 15 . Over the past few years, the CFD‐DEM method has been widely applied in erosion‐related problems 10,16–21 . Xiong et al 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these techniques, the coupled computational fluid dynamics and discrete element method (CFD‐DEM) has raised much attention because of its advantages in computational efficiency, especially compared with the Lattice Boltzman‐DEM coupling (LB‐DEM) 14 and pore‐scale finite volume‐DEM coupling (PFV‐DEM) 15 . Over the past few years, the CFD‐DEM method has been widely applied in erosion‐related problems 10,16–21 . Xiong et al 2 .…”
Section: Introductionmentioning
confidence: 99%
“…15 Over the past few years, the CFD-DEM method has been widely applied in erosion-related problems. 10,[16][17][18][19][20][21] Xiong et al 2 conducted simulations to study macroscopic, microscopic, and mechanical characteristics during suffusion. They found that the greater the angle between flow and gravity, the harder it was for internal erosion to occur and continue.…”
mentioning
confidence: 99%
“…The purpose of this work is to examine the effect of particle orientation on the flow characteristics and derive a pressure drop tensor across an anisotropic packed bed. As recommended by Hoffmann, the crushed rock was represented as an ellipsoidal to model the bed [12]. The ellipsoidal shape has the same volume and aspect ratio as the averages measured for roughly 100 rocks.…”
Section: Objectives and Methodologymentioning
confidence: 99%
“…Particle size and shape have a significant effect on the pressure drop. For that reason, several particle shapes have been proposed to represent crushed rocks, including bricks, connected spheres, and ellipses [10] - [12]. The ellipsoidal shapes were more effective at presenting the crushed rocks than the other shapes [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation